Intergenerational mobility in Norway, 1865-2011 - Jørgen Modalsli (Statistics Norway, Research Department, 2015)
There are large differences in intergenerational mobility between countries. However, little is known about how persistent such differences are, and how they evolve over time. This paper constructs a data set of 835,537 linked father-son pairs from census records and documents a substantial increase in intergenerational occupational mobility in Norway between 1865 and 2011. The increase is most pronounced in nonfarm occupations. The findings show that long-run mobility developments previously described for the US and UK are not necessarily representative for other countries, and that high mobility in a given country today need not reflect high mobility before industrialization.
Keywords: J62; N33; N34; 330; Intergenerational mobility; Occupations; Mobility measurement; Economic history